The Impact Of It Social Network Path In The Students Of Community - Arnes Yuli Vandika (Bandar Lampung University, 2015)
Most social media network users in the world are the ones generation The young are born in the late 80's or early 90's. Nielsen (2011) report user that dominated by women and 18-34 year-old is the most active in social media networking. They use rapidly new media and the latest technology. They are interested and more interested in everything related to the Internet and its applications. they are very active and tend to engage with social networks such as page Facebook, Twitter, Google+ or Path. This study aims to know the definite acceptance and user experience in using social media especially among university students using Technology Acceptance Model (TAM) by Davis (1989) as a theoretical background.additional change that is a factor and the circuit connection between the personal and the social has been added to the model origin.